Validation of CFD simulations of the flow around a full-scale rowing blade with realistic kinematics - Robert, Y.; Leroyer, A.; Barré, S.; Queutey, P.; Visonneau, M. (Journal of Marine Science and Technology, 2019)
This article deals with the validation of the modelling and numerical simulation of a rowing stroke, by means of CFD. Simplified but realistic strokes were performed in a towing tank with a rotating arm and a real flexible oar. Those laboratory conditions are better controlled than those of in situ trials. An FSI procedure is developed to take into account the oar bending, which is essential in the physics of this flow. The results show that this numerical framework is able to reproduce qualitatively the real flow including the breaking of the free surface around the blade and the transport of the air cavity behind it. The profiles of forces are well reproduced, with propulsive forces overestimated by 5-12% for their maxima. The study also focuses on the computation of the uncertainties. It is highlighted that, even for this well-controlled experimental equipment, the uncertainties on the quantities of interest are of about 11%. In other words, the experimental uncertainty covers the numerical errors. So, this numerical modelling is validated and can be used for design and optimisation of blades and oars, or to contribute to the better understanding of the boat-oar-rower system and its dynamics.